Influence of Metro Vehicle Air Compressor Suspension Methods on Modal Parameters and Optimization of Vibration Reduction Forms - CHEN Lei; LIU Zhonghua; LIU Zheng (Chengshi guidao jiaotong yanjiu)
［Objective］ Air compressor is one of the main sources for metro vehicle vibration excitation. Reasonable modal matching design for air compressor is conducive to reducing the vehicle body vibration and noise, thereby improving the riding comfort of the vehicle. ［Method］ A finite element model of air compressor and its frame is established by using ANSYS finite element software. The influence of the two-stage vibration reduction suspension method for metro vehicle air compressor on its modal parameters is calculated and analyzed, and the above-mentioned suspension method between air compressor and its frame is optimized in the design. ［Result & Conclusion］ For the air compressor with a two-stage vibration reduction system, unreasonable suspension method is likely to cause the modal frequencies of air compressor and its frame close to the excitation frequency of the compressor, thus resulting in resonance. When rubber is adopted for the first-stage vibration reduction between the motor end, the compressor end and the frame, and rigid connection adopted for the second-stage vibration reduction between the air compressor frame and the vehicle body mounting seat, the modal frequencies of air compressor and its frame can effectively avoid excitation frequency of the air compressor, preventing the violent vibration of air compressor and its frame caused by the coincidence of the excitation frequency and the modal frequency.